Environmental Sustainability Practices, Social Responsibility, and Effective Management of Colleges of Education in Anambra State Nigeria - Ekemezie Ekene; Anyachebelu Uzoma Miriam (Action Research Journal Indonesia (ARJI), 2024)
The objective of the study was to assesses the impact of environmental sustainability practices, and social responsibility on effective management of colleges of education in Anambra State, Nigeria. Three research questions and three research hypotheses were raised. The study utilized a quantitative research design, targeting academic and administrative staff across various institutions to collect numerical data on their perceptions. A stratified random sampling technique selected a representative sample of 124 respondents. Data were gathered using a validated structured questionnaire, with reliability confirmed through Cronbach's alpha coefficients above 0.90. Data collection occurred both in-person and electronically to ensure anonymity. Descriptive statistics provided understanding into participants' perceptions, while Pearson correlation analysis evaluated the relationship between effective management and environmental sustainability practices. The findings revealed a significant positive correlation between environmental sustainability practices and effective management, indicating that improved environmental practices enhance governance outcomes. Additionally, social responsibility was found to positively influence perceptions of management effectiveness, highlighting the importance of ethical practices in public service delivery. Economic stability also showed a moderate positive correlation with effective management, emphasizing its role in fostering effective governance. The study concludes that addressing these interconnected factors is essential for enhancing management effectiveness in colleges of education. Future research should explore the long-term effects of these factors on governance and develop frameworks for integrating them into public administration practices.